Design of Nickel-Containing Nanocomposites Based on Ordered Mesoporous Silica: Synthesis, Structure, and Methylene Blue Adsorption - Tatyana Kouznetsova; Andrei Ivanets; Vladimir Prozorovich; Polina Shornikova; Lizaveta Kapysh; Qiang Tian; László Péter; László Trif; László Almásy (Gels, 2024)
Mesoporous materials containing heteroelements have a huge potential for use as catalysts, exchangers, and adsorbents due to their tunable nanometer-sized pores and exceptionally large internal surfaces accessible to bulky organic molecules. In the present work, ordered mesoporous silica containing Ni atoms as active sites was synthesized by a new low-temperature method of condensation of silica precursors on a micellar template from aqueous solutions in the presence of nickel salt. The homogeneity of the resulting product was achieved by introducing ammonia and ammonium salt as a buffer to maintain a constant pH value. The obtained materials were characterized by nitrogen sorption, X-ray and neutron diffraction, scanning electron microscopy, infrared spectroscopy, and thermal analysis. Their morphology consists of polydisperse spherical particles 50–300 nm in size, with a hexagonally ordered channel structure, high specific surface area (ABET = 900–1200 m2/g), large pore volume (Vp = 0.70–0.90 cm3/g), average mesopore diameter of about 3 nm, and narrow pore size distribution. Adsorption tests for methylene blue show sorption capacities reaching 39–42 mg/g at alkaline pH. The advantages of producing nickel silicates by this method, in contrast to precipitation from silicon alkoxides, are the low cost of reagents, fire safety, room-temperature processing, and the absence of specific problems associated with the use of ethanol as a solvent, as well as the absence of the inevitable capture of organic matter in the precipitation process.